Information security theory and practice : 13th IFIP WG 11. 2 International Conference, WISTP 2019, Paris, France, December 11-12, 2019, Proceedings /: 13th IFIP WG 11. 2 International Conference, WISTP 2019, Paris, France, December 11-12, 2019, Proceedings. (2020) - Unknown
No abstract available